Dynamic impact of social stratification and social influence on smoking prevalence by gender: An agent-based model. (December 2015) - Chao, Dingding; Hashimoto, Hideki; Kondo, Naoki
Abstract: Smoking behavior is tightly related to socioeconomic status and gender, though the dynamic and non-linear association of smoking prevalence across socioeconomic status and gender groups has not been fully examined. With a special focus on gender-bound differences in the susceptibility to social influence of surrounding others' behaviors, we developed an agent-based model to explore how socioeconomic disparity between and within gender groups affects changes in smoking prevalence. Our developed base model reasonably reproduced the actual trend changes by gender groups over the past 5 years in Japan. Counterfactual experiments with the developed model revealed that closing within- and between-gender disparities in socioeconomic status had a limited impact on reducing smoking prevalence. To the contrary, greater socioeconomic disparity facilitated the reduction in prevalence among males, but it impeded that reduction in females. The counterfactual scenario with equalizing gender-bound susceptibility to social influence among women to men's level showed a dramatic reduction in female prevalence without changing the reduction in male prevalence. Simulation results may provide alternative explanation of the growing disparity in smoking prevalence despite improved welfare equality observed in many developed countries, and suggest that redistribution policies may have side effects of widening health gap. Instead, social policy to reduce social pressures to smoking and support interventions to enhance resilience to the pressure targeting the vulnerable population (in this study, women) would be a more effective strategy in combating the tobacco epidemic and closing the health gap. Highlights: An ABM to explore how SES disparity and gender affects changes in smoking. A policy to close SES disparity may have limited impact on prevalence reduction. Intervention to enhance resilience to social influence would be effective.